The effect of using the Balanced Scorecard (BSC) on reducing the financial and administrative corruption in Iraqi Government Units - Alamry, Saoud Jayed Mashkour; Al-Attar, Hayder Abbas; Salih, Abdulhadi Salman (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This research aims to explore the importance application the Balanced Scorecard (BSC) to the accountants and auditors in government units, which in turn contributes to raising the efficiency of scientific and practical performance as one of the fights against financial and administrative corruption suffered by the majority of the government units in Iraq. Research methodology: This research used a statistical method in the analysis and measurement by using (SPSS) program to extract the necessary statistical indicators to determine the impact of the independent variables (BSC) on the dependent variable (financial and administrative corruption). Results: There is a significant correlation between the Balanced Scorecard (BSC) and the professional performance efficiency of accountants and auditors, as well as a significant correlation between the Balanced Scorecard (BSC) and the fight against financial and administrative corruption. Limitations: There is a conflict between legislation, laws, and administrative controls in some measures of the balanced scorecard. Besides that, the lack of transparency and impartiality of the employees responsible for setting the balanced scorecard measures, as well as the other parties Contribution: Find recommended the need to apply the balanced scorecard in the evaluation of the efficiency and improve the performance of the work of accountants and auditors, and the need for government units in the city of Samawah-Iraq, the establishment of training courses, seminars, workshops, and giving lectures specialized in combating financial and administrative corruption that is prevalent in the majority of government units.